Penerapan Model Think Talk Write (TTW) untuk Meningkatkan Hasil Belajar Matematika - Timbul Yuwono; Riski Nur Istiqomah Dinnullah; Jemi Hadrimus (RAINSTEK : Jurnal Terapan Sains & Teknologi, 2022)
Abstrac: The aims of this study were (1) to apply the Think Talk Write learning model to improve mathematics learning outcomes for class VIII students at SMP PGRI 2 Lawang Malang, (2) to determine the response of class VIII students at SMP PGRI 2 Lawang Malang towards the application of the Think Talk Write learning model. . This research is a qualitative research with the type of classroom action research (CAR). The subjects in this study were class VIII students of SMP PGRI 2 Lawang Malang for the 2019/2020 academic year, totaling 25 students. Data collection techniques used are observation, tests, interviews and field notes. Data analysis used qualitative analysis. The results of this study indicate that (1) the percentage of students' learning mastery classically increased from 72% of students in the value of action I to 92% in action II of a total of 75 students or more, (2) students gave a very positive response in learning mathematics by using the Think Talk Write learning model. Thus, the Think Talk Write learning model can improve the mathematics learning outcomes of eighth grade students of SMP PGRI 2 Lawang Malang. Keywords: Think Talk Write Learning Model, Mathematics Learning Outcomes Abstrak: Tujuan penelitian ini adalah (1) untuk menerapkan model pembelajaran Think Talk Write untuk dapat meningkatkan hasil belajara matematika siswa kelas VIII SMP PGRI 2 Lawang Malang, (2) untuk mengetahui respon siswa kelas VIII SMP PGRI 2 Lawang Malang terhadap penerapan model pembelajaran Think Talk Write. Penelitian ini merupakan penelitian kualitatif dengan jenis penelitian tindakan kelas (PTK). Subyek dalam penelitian ini adalah siswa kelas VIII SMP PGRI 2 Lawang Malang tahun ajaran 2019/2020 yang berjumlah 25 orang siswa. Teknik observasi, tes, wawancara dan catatan lapangan adalah teknik pengumpulan data yang digunakan. Analisis kualitatif yang digunakan untuk menganalisis data. Hasil penelitian ini menunjukan bahwa (1) persentase ketuntasan belajar siswa secara klasikal meningkat dari 72% siswa pada nilai tindakan I menjadi 92% pada tindakan II dari total seluruh siswa 75 atau lebih, (2) respon yang sangat positif dari siswa dalam pembelajaran matematika dengan menggunakan model pembelajaran Think Talk Write. Dengan demikian model pembelajaran Think Talk Write dapat meningkat hasil belajar matematika siswa kelas VIII SMP PGRI 2 Lawang Malang. Kata Kunci: Pembelajaran Model Think Talk Write (TTW), Hasil Belajar Matematika